PENGARUH MEKANISME CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PADA PERIODE 2018-2020 - Deby Dwi Rahma Gusti; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2022)
Accounting conservatism is useful for limiting the opportunistic actions of managers in financial reporting to avoid overstatement in reporting earnings and assets. The purpose of this study is to identify and provide empirical evidence regarding the effect of corporate governance mechanism and leverage on accounting conservatism. Corporate governance mechanism in this study is proxied by independent commissioners, institutional ownership, managerial ownership, and the audit committee. Leverage in this study is proxied by Debt to Asset Ratio (DAR), and accounting conservatism in this study is proxied by Market to Book Ratio (MTBR).The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The sampling method in this sudy used purposive sampling. The number of companies used as research samples amounted to 27 manufacturing companies. The method of analysis in this study uses the method of multiple linear analysis.The results showed that independent commissioners, institutional ownership, managerial ownership, and the audit committee had a negative and insignificant effect on accounting conservatism. Leverage had a negative and significant effect on accounting conservatism. The results showed that the corporate governance mechanism and leverage simultaneously had a significant effect on accounting conservatism.